Are Agroecological Farms Resilient? Some Results Using the Tool SHARP-FAO in Costa Rica - Molina-Murillo, Sergio A. (2017)
Considering the current variability of climate, it is urgently required to measure and monitor climate resilience to inform and empower small agrosilvopastoral producers. Although there are other ways to measure resilience, the new SHARP tool developed by FAO allows the identification, measurement and prioritization of actions to improve climate resilience in a participatory manner, taking into account the interests of producers. In coordination with the FAO implementation team in Rome, the questionnaire and the matrix for resilience assessment were translated and used to assess 16 agroecological farms located within the Central Valley of Costa Rica. Once the data were collected and entered into SHARP, three analyses were carried out: 1) comparing the profile of the farms studied with indicators at a national level; 2) a gap analysis to identify opportunities for improvement in terms of climate resilience; 3) an analysis to adapt the tool to the national context. Although the farms selected for the study are recognized as agroecological, their average level of resilience (x̄=15,25; s=1,16) suggests the need to implement management practices that contribute to the construction of more resilient ecosystems.